Association between physical activity and alcohol consumption: sociodemographic and behavioral patterns in Brazilian adults. (16th November 2018) - Werneck, André O; Oyeyemi, Adewale L; Szwarcwald, Célia L; Silva, Danilo R
ABSTRACT: Background: Our aim was to investigate the association between physical activity and alcohol consumption, as well as the sociodemographic and behavioral patterns of this association in a representative sample of Brazilian adults. Methods: Data from the Brazilian Health Survey (PNS), a nationally representative survey conducted in 2013 ( n = 60 202; age≥18 years), were used. Time spent in leisure physical activity, alcohol consumption as well as sociodemographic (chronological age, educational status and skin color) and associated behavioral factors (TV viewing and tobacco smoking) were collected via interview. Logistic regression models were used for the main analyses. Results: Prevalence of weekly and almost daily alcohol consumption were 29.5% and 6.7% for men and 12.0% and 1.0% for women respectively. Adults with weekly alcohol consumption were more likely to be classified as physically active [young: men=OR:1.20 (CI 95%:1.02–1.39), women= OR:2.33 (CI 95%:1.92–2.82); middle-aged: men= OR:1.46 (CI 95%: 1.17–1.82), women= OR:1.75 (CI 95%:1.38–2.22); older: men= OR:1.83 (CI 95%:1.27–2.66), women= OR:2.11 (CI 95%: s1.26–3.52)], when compared to adults with no alcohol consumption. Almost daily alcohol consumption was associated with lower physical activity among young and middle-aged adults but with higher physical activity among older adults of both sexes and young women. Conclusions: Weekly alcohol consumption was associated with a higher level of physical activity among young, middle aged and older adults.